Fast Settling Time & Low Power Based Construction of On-Chip Inverter: An Experimental Approach - Prasad Tripathy, Hara; Pattanaik, Priyabrata; Kumar Kamilla, Susanta (International Journal of Psychosocial Rehabilitation, 2025)
The three essential constraints such as “power”, “speed” and “noise margin” are responsible for the enactment of the “CMOS inverter”. These constraints analyses outcome by the W/L proportion by numerous transistors. These constraints also aid in analysing the influence by modification in particular technology. For attaining optimum results different designs are required for the different technologies. Supplementary job of “capacitive load” is additionally contemplated & it had been perceived that a particular capacitive load explicit estimation of angle proportion that provides an ideal estimation of intensity scattering with quick settling. Work performed could be extremely useful for circuit planner as this work has considered on-chip CMOS inverter under various burden conditions and utilizing various innovations.